When Eutectics Meet Plasmonics: Nanoplasmonic, Volumetric, Self‐Organized, Silver‐Based Eutectic. Issue 3 (16th December 2014) - Sadecka, Katarzyna; Gajc, Marcin; Orlinski, Krzysztof; Surma, Hancza B.; Klos, Andrzej; Jozwik‐Biala, Iwona; Sobczak, Kamil; Dluzewski, Piotr; Toudert, Johann; Pawlak, Dorota A.
<x xml:space="preserve">Abstract</x> Due to the development of novel manufacturing technologies and the increasing availability of nano‐/micromaterials, plasmonics has become an emerging field in photonics research. Although the fabrication of metallic elements has already been widely demonstrated, the development of 3D plasmonic materials is progressing slowly. This paper reports the development of a self‐organized, 3D nanoplasmonic eutectic composite that exhibits localized surface plasmon resonance at 595 nm. This eutectic composite is produced by directional solidification with the micro‐pulling‐down method and consists of a 3D, multiscale network of silver, nanometer‐thick, micron‐long sheets, and triangular cross‐section microprecipitates embedded in a crystalline bismuth oxide matrix. Annealing at 600 °C further refined the structure and introduced metallic nanoparticles that exhibited plasmonic resonance in the optical region of the spectrum. This is the first demonstration of plasmonic behavior in a eutectic‐based composite, which is engineered specifically for this purpose using a self‐organization mechanism.